2019
DOI: 10.1002/jsfa.9855
|View full text |Cite
|
Sign up to set email alerts
|

Physical, sensorial and bioactive characteristics of white chocolate with encapsulated green tea extract

Abstract: BACKGROUND Many studies have described cocoa polyphenols as being bioactive compounds with a potential positive effect on human health. Although dark chocolate is a most powerful source of antioxidants, their content is lower in milk chocolate; conversely, in white chocolate the fat‐free cocoa solids are omitted. The aim of this study was to increase polyphenol content and antioxidant capacity of white chocolate by adding encapsulated green tea extract (GTE) in amounts of 60, 80 and 100 g kg−1. RESULTS GTE inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 20 publications
4
25
0
Order By: Relevance
“…Other studies have also reported that the addition of fruit or other phenolic-rich plants to chocolates either increase or decrease antioxidant activity evaluated by FRAP and DPPH assays [32,33,41,46]. These distinct differences may be attributed to the increased interaction between phenolics and other compounds, including carbohydrates, sweeteners, and proteins, present in chocolate and in fruits or vegetables.…”
Section: Antioxidant Activitymentioning
confidence: 97%
See 2 more Smart Citations
“…Other studies have also reported that the addition of fruit or other phenolic-rich plants to chocolates either increase or decrease antioxidant activity evaluated by FRAP and DPPH assays [32,33,41,46]. These distinct differences may be attributed to the increased interaction between phenolics and other compounds, including carbohydrates, sweeteners, and proteins, present in chocolate and in fruits or vegetables.…”
Section: Antioxidant Activitymentioning
confidence: 97%
“…However, the values of parameter b* remained more similar. Generally, the addition of freeze-dried phenolic-rich plant powder to DCH, DCH98S, DCH98ESt or MCH significantly (p < 0.05) brightened the color on the surface of enriched chocolates compared to the control ones, which could be attributed to some changes in the crystal structure of cocoa butter (polymorphism) [32]. On the other hand, there were only slight differences for the a* and b* parameters between the control chocolates and the enriched chocolates of the same type.…”
Section: Water Content and Activity And Color Of Chocolatesmentioning
confidence: 99%
See 1 more Smart Citation
“…One of their peers, Jayawardana et al (2019), found that incorporation of green tea extract as an antioxidant on uncured pork sausages did not impact significantly on sensory profile of the sausages. Likewise, Lončarević et al (2019) mentioned that inclusion of green tea extract in white chocolate did not impart any anomalous changes in its olfactory aspects. All these studies results were in accordance with the current study outcomes.…”
Section: Sensory Acceptancementioning
confidence: 99%
“…Thus, the functionality of white chocolate is very low compared to dark and milk chocolate, and functional food development studies associated with white chocolate are very limited [ 7 ]. Our previous investigations were focused on the enrichment of white chocolate with polyphenol compounds by adding 6–10% of blackberry encapsulate and encapsulated green tea extract [ 10 , 11 ]. Barišić et al [ 12 ] showed that cocoa shells may be used in chocolate production as a source of dietary fiber.…”
Section: Introductionmentioning
confidence: 99%